Linear delta expansion applied to the O'Raifeartaigh model - Abdalla, M. C. B. [UNESP]; Helayel-Neto, J. A.; Nedel, Daniel L.; Senise, Carlos R. [UNESP] (Amer Physical Soc, 2009)
We reassess the method of the linear delta expansion for the calculation of effective potentials in superspace, by adopting the improved version of the super-Feynman rules in the framework of the O'Raifeartaigh model for spontaneous supersymmetry breaking. The effective potential is calculated using both the fastest apparent convergence and the principle of minimal sensitivity criteria and the consistency and efficacy of the method are checked in deriving the Coleman-Weinberg potential.